Benefits of 8-week fitness programs on health and fitness parameters (Beneficios de los programas de fitness de ocho semanas en parámetros de salud y fitness) - Francisco Campos; Sixto González-Víllora; David González Gómez; Fernando Manuel Lourenço Martins (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract: considering health and fitness enhancements as the main reasons for engaging in physical activity, the growing number of sport participants in health or fitness centers, as well as the trends in fitness in 2018, the aim of this work is to analyze the benefits of five different fitness programs: G1) diet and no-exercise; G2) diet and weight training (WT); G3) diet and high intensity power training (HIPT); G4) diet and indoor cycling; G5) diet and boxing; on health and fitness parameters. Five groups were created and participants were evenly and randomly distributed (G1 to G5: n = 50; 25 f, 33.96 ± 3.42 years). In the first analysis, paired samples t test was used to compare the dependent variables within each group separately, from pre-to post-test. In the second analysis, one-way ANOVA was used to compare the selected variables between the different groups, at pre-and post-test; following, post-hoc continuation test was performed where the ANOVA detected significant differences. When the main reason for practice was loss of weight and fat mass, HIPT and boxing produced better results than the other programs. For the increase of fat-free mass, WT presented the best results. Regarding fitness parameters, WT was the activity that presented higher results in the increase of lower explosive strength and upper maximum strength, with significant statistical differences between pre- and post-test. Fitness instructors can use this information to adapt, choose and prescribe adequate activities, according to participants’ main reasons for practice; therefore, increasing their perception of quality, satisfaction, as well as their loyalty intention.